Foam-mat drying of passion fruit aril - Khamjae, T. (2019)
This study was aimed to determine the effect of methylcellulose concentration and whipping time on the properties of passion fruit aril foam. The effect of foam-mat drying conditions on moisture diffusivity, physicochemical, microbiological and antioxidant properties of the dried product was also investigated. Passion fruit aril incorporated with methylcellulose at a mass concentration of 0.75%, 1.5%, 2.25% and 3.0% was whipped for 0 min, 10 min, 20 min and 25 min. The passion fruit aril foam mats (1-mm, 2-mm and 3-mm thick) were dried at 60°C,70°C and 80°C with a constant air velocity of 0.5 m/s. The optimum condition for forming foam was 2.25% methylcellulose after 25 min whipping as it provided the highest foam expansion (187.25%) and stability as well as the lowest foam density (0.41 g/ml). Drying the passion fruit aril foam chiefly occurred in the falling rate period. Effective moisture diffusivity increased with increasing temperature and foam thickness. This value ranged from 1.06×10-7 m2/s to 1.01×10-6 m2 /s. Passion fruit aril foam (1-mm thick) dried at 70°C for 90 min showed the highest amount of ascorbic acid and β-carotene as well as antioxidant activity (assayed by DPPH and ABTS methods) (p≤0.05). Based on microbial counts, freshly prepared foam-mat dried passion fruit aril samples were considered safe.